Pengaruh Kualitas Produk, Promosi, Dan Harga Terhadap Keputusan Pembelian (Survei Pada Konsumen Apay Store Solo) - Yofi Yanti; Sumaryanto; Retno Susanti (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to analyze the significance of the influence of product quality, promotion, and price on purchasing decisions of Apay Store Solo consumers. This study is a survey of Apay Store Solo consumers. The types of data used are qualitative and quantitative data. The data sources used are primary and secondary data. The population in this study were Apay Store Solo consumers. The number of samples used in this study was 100 people. The sampling technique used the purposive sampling method, namely samples selected with certain considerations. Data collection techniques used questionnaires, literature studies and observations. Data analysis used multiple linear regression tests, t tests, F tests and determination coefficient tests Based on the statistical data analysis of the validity test and reliability test of the indicators in this study are valid and the variables are reliable. In the classical assumption test of the multicollinearity free regression model. The results showed that product quality did not have a significant effect on purchasing decisions, promotion did not have a significant effect on purchasing decisions, price had a significant effect on purchasing decisions. The results of the F test show a calculated F value of 43.716 with a significance value of p-value 0.000 <0.05, which means that Ho is rejected and Ha is accepted. The results of the determination coefficient are 0.564, meaning that the influence given by the independent variables, namely product quality, promotion and price on the dependent variable, namely purchasing decisions, is 56.4%. The rest (100% - 56.4%) = 43.6% is explained by other variables out]side the model.